2020
DOI: 10.1186/s13033-020-00385-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of mental healthcare in Cambodia: barriers and opportunities

Abstract: Background: Despite the increasing recognition globally of the importance of mental health for sustainable development, significant barriers remain to developing mental health services in low-and middle-income countries. This study explored the particular barriers and opportunities for developing mental health services in Cambodia and how these compared with those described in other low-and middle-income countries. Methods: For this qualitative study, 18 experienced mental health professionals from different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Poor health literacy, especially a lack of understanding about mental health, was reported in six studies (Hall et al, 2019;Nguyen et al, 2019;Parry et al, 2020;Putri et al, 2021;Subramaniam et al, 2021;Trang et al, 2021;Zay Hta et al, 2021). Hall et al (2019) and Zay Hta et al ( 2021) reported that the lack of available information contributed to the poor knowledge held by the SEA population, while Subramaniam et al (2021) identified that mental health education was a low priority in schools and workplaces.…”
Section: Poor Health Literacymentioning
confidence: 99%
“…Poor health literacy, especially a lack of understanding about mental health, was reported in six studies (Hall et al, 2019;Nguyen et al, 2019;Parry et al, 2020;Putri et al, 2021;Subramaniam et al, 2021;Trang et al, 2021;Zay Hta et al, 2021). Hall et al (2019) and Zay Hta et al ( 2021) reported that the lack of available information contributed to the poor knowledge held by the SEA population, while Subramaniam et al (2021) identified that mental health education was a low priority in schools and workplaces.…”
Section: Poor Health Literacymentioning
confidence: 99%
“…The The 1970's genocide in Cambodia led to death of a third of the population and the destruction of all infrastructure including healthcare (Parry et al, 2020). Parry et al (2020) describe the 1991 Paris Peace Agreement, providing the stability to begin to rebuild the nation, including health care. Nongovernmental organisations (NGO) have played a major role in the rebuilding of mental healthcare (Leng, 2018).…”
Section: Charlotte Wearsmentioning
confidence: 99%
“…The provision of health care in Cambodia is very different to Western nations and this can present extra challenges to the counsellor when a client has health difficulties requiring medical care. For example, in Cambodia there are currently 60 psychiatrists to serve a population of around 16 million (Parry et al, 2020). The basics of diet, exercise and sleep can also present extra challenges.…”
Section: Physical Healthmentioning
confidence: 99%
“…The mental health needs of the Khmer community compel a caring global response. Anxiety and depression, both considered common mental health conditions, reportedly affect a high percentage of Cambodians, with up to 80% and 53% meeting criteria, respectively (Parry et al, 2020). The prevalence of post-traumatic stress disorder (PTSD) in the Cambodian population has been reported at rates up to 86% (Parry et al, 2020), and substance use disorders are estimated to affect 41.9% of the population, although the true rate is likely higher (Saing et al, 2020).…”
Section: Introductionmentioning
confidence: 99%